2021
DOI: 10.3389/fmolb.2021.721533
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline Prevents LPS-Induced Inflammatory Response via Nicotinic Acetylcholine Receptors in RAW 264.7 Macrophages

Abstract: The cholinergic anti-inflammatory pathway plays an important role in controlling inflammation. This study investigated the effects of varenicline, an α7 nicotinic acetylcholine receptor (α7nAChR) agonist, on inflammatory cytokine levels, cell proliferation, and migration rates in a lipopolysaccharide (LPS)-induced inflammation model in RAW 264.7 murine macrophage cell lines. The cells were treated with increasing concentrations of varenicline, followed by LPS incubation for 24 h. Prior to receptor-mediated eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This may indicate that MST‐312 could affect the tumor immune microenvironment by suppressing virus replication in virus‐related HCC. In a similar role, varenicline can prevent LPS‐induced inflammatory response in RAW 264.7 Macrophages 48 . These results suggest that the two drugs may affect the tumor immune microenvironment by controlling chronic inflammation in virus‐related HCC.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This may indicate that MST‐312 could affect the tumor immune microenvironment by suppressing virus replication in virus‐related HCC. In a similar role, varenicline can prevent LPS‐induced inflammatory response in RAW 264.7 Macrophages 48 . These results suggest that the two drugs may affect the tumor immune microenvironment by controlling chronic inflammation in virus‐related HCC.…”
Section: Discussionmentioning
confidence: 67%
“…In a similar role, varenicline can prevent LPS-induced inflammatory response in RAW 264.7 Macrophages. 48 These results suggest that the two drugs may affect the tumor immune microenvironment by controlling chronic inflammation in virusrelated HCC. As presented in Figure 7, CGP57380, the screened small-molecule drug, inhibited HCC cell growth and exemplified antitumor function in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, varenicline significantly reduced LPS-induced cell migration through α7nAChR, while decreasing cell proliferation independently of nAChR. Our findings suggested that varenicline attenuates LPS-induced inflammation by activating α7nAChRs, eventually reducing cytokine production and cell migration ( Baris et al, 2021b ). Moreover, CAP-inducing agents; CDP-choline and choline, reduce the inflammation process through the COX pathway in LPS-induced endotoxemia in rats.…”
Section: Introductionmentioning
confidence: 67%
“…In the first group, cells were treated with LPS (Escherichia coli, Sigma Aldrich L4130 0111: B4) at various concentrations (1-2 and 3 μg/mL) to determine effective concentration at which cytokines are released (Parrish et al, 2008). In the second group, cells were pretreated with varenicline tartrate (Sigma-Aldrich PZ0004) with increasing concentrations (0.1-0.3-0.8-1-3-10 μM) 30 min prior to LPS administration to were applied 30 min before varenicline and LPS (Yang et al, 2015;Yi et al, 2015;Baris et al, 2021b). RAW 264.7 cells at passage #5 were originally from ATTC (gift).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with our experimental protocol, previous studies that attempted to evaluate the contribution of α7nAChR to macrophage migration utilized macrophage-like cell lines, wild-type cell phenotype (no α7nAChR-knockout), and the most importantly, a simplified 2D transmigration setup without chemokine gradients or protein coatings. For example, the ability of the α7nAChR agonists (PHA-543613 and varenicline) to decrease migration of RAW264.7 cells was demonstrated by testing cell transmigration through uncoated trans-well membranes (Boyden chambers) without a chemokine gradient [ 52 , 53 ]. Similar results were obtained by others who showed that acetylcholine can inhibit LPS-induced RAW264.7 cell migration.…”
Section: Discussionmentioning
confidence: 99%